2003
DOI: 10.1177/154405910308200715
|View full text |Cite
|
Sign up to set email alerts
|

An Involvement of Trigeminal Mesencephalic Neurons in Regulation of Occlusal Vertical Dimension in the Guinea Pig

Abstract: Although the occlusal vertical dimension (OVD) is strictly controlled, the neuronal mechanism of its regulation is still unclear. We hypothesize that neurons in the trigeminal mesencephalic nucleus (MesV) play an important role in the regulation of the OVD, because the MesV receives the projection from jaw-closing muscle spindles and periodontal mechanoreceptors. We measured the temporal OVD change in the guinea pig to study the effects of MesV lesions on the OVD. OVD-raised animals without MesV lesions showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…It has been repeatedly suggested that inputs from jaw muscle spindles would be involved in the physiological mechanism of OVD regulation (e.g., Yagi et al, 2003;Zhang et al, 2003). Thus, sensory feedback from the jaw muscle could be blamed for the instability and relapse of occlusal treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been repeatedly suggested that inputs from jaw muscle spindles would be involved in the physiological mechanism of OVD regulation (e.g., Yagi et al, 2003;Zhang et al, 2003). Thus, sensory feedback from the jaw muscle could be blamed for the instability and relapse of occlusal treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies suggest the OVD to be strictly controlled (Yagi et al, 2003), and that this control would be exerted, at least in part, by inputs from jaw-muscle spindles (Zhang et al, 2003), we have recently demonstrated that masseter muscle spindles already start to show some degree of functional plasticity 5 days after the establishment of an increased OVD (iOVD) condition (Yabushita et al, 2005); i.e., some parameters of muscle-spindle function, particularly those related to the receptor's sensitivity, were affected by changes in OVD. In this study, we tested for the possibility of functional recovery in masseter muscle spindles following longer periods of observation after iOVD.…”
Section: Introductionmentioning
confidence: 99%
“…The periodontal ligament not only regulates occlusal force associated with muscle spindles in the closer jaw muscles (Zhang et al 2003;Lund and Kolta 2006) but also perceives nociception mediated by free nerve endings of Aδ and C fibers, which originate from the trigeminal ganglion (Byers 1985) and project to the trigeminal spinal Vi and Vc (subnuclei interpolaris and caudalis, respectively; Sugimoto et al 1997;Watanabe et al 2002). A portion of these nociceptive fibers contain calcitonin gene-related peptide and/or galanin, whose expression is increased by experimental tooth movement (ETM; Kvinnsland and Kvinnsland 1990;Deguchi et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, the reduction of OVD may be attributed to the total changes in the upper and lower teeth length. Zhang et al (12) reported that the tooth-grinding ability of guinea pigs after increasing their bite was impaired by the destruction of the trigeminal mesencephalic nucleus in bite-raised animals. Muscle spindle afferents of the jaw-closing muscles may be closely involved in OVD adjustment.…”
Section: Temporal Change In Ovdmentioning
confidence: 99%